PENGARUH PENDIDIKAN KEWIRAUSAHAAN DAN KARAKTERISTIK PSIKOLOGIS TERHADAP INTENSI BERWIRAUSAHA DENGAN SIKAP BERWIRAUSAHA SEBAGAI VARIABEL MEDIASI (STUDI PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS KHAIRUN) - Karepesina, Dandy; Zulkifli, Zulkifli; Rajak, Adnan (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Khairun, 2022)
Objective: This study aims to determine the effect of entrepreneurship education and psychological characteristics on entrepreneurial intentions through entrepreneurial attitudes. This research is a quantitative research. The population in this study is the students of the faculty of economics and business. The number of research samples is 91 respondents. The data analysis technique used in this study is SEM analysis using Smart Partial Least Square (PLS) version 3 as a statistical test tool.Methodology: The analytical model used are Structural Equation Modeling with SMART PLS as tools for the statistical test. Data collection tools used are questionnaires and interviews, and the number of respondents was 91 employee.Finding: H1, H5, H6, and H7 are rejected, while H2, H3, and H4 are accepted at the 5% confidence level.Conclusion: The results of this study indicate that: (1) Entrepreneurship Education has a positive but not significant effect on entrepreneurial attitudes; (2) Psychological characteristics have a positive and significant effect on entrepreneurial attitudes; (3) Entrepreneurship Education has a positive and significant effect on entrepreneurial intentions; (4) Psychological characteristics have a positive and significant effect on entrepreneurial intentions; (5) Entrepreneurial attitude does not have a significant effect on entrepreneurial intentions (6) Entrepreneurial attitude does not mediate the effect of entrepreneurship education on entrepreneurial intentions; (7) Entrepreneurial attitude does not mediate the influence of psychological characteristics on entrepreneurial intentions.